IRAC: Mode of action classification and insecticide resistance management - Sparks, Thomas C.; Nauen, Ralf (Pesticide biochemistry and physiology, 2015)
•Insecticide resistance is expanding – >580 species resistant to >1 insecticides.•IRAC – promotes development and use of standardized bioassays for resistance detection.•IRAC – focused on long term insecticide resistance management.•IRAC – information on insecticide modes of action (MoA).•MoA classification provides the basis for effective resistance management. Insecticide resistance is a long standing and expanding problem for pest arthropod control. Effective insecticide resistance management (IRM) is essential if the utility of current and future insecticides is to be preserved. Established in 1984, the Insecticide Resistance Action Committee (IRAC) is an international association of crop protection companies. IRAC serves as the Specialist Technical Group within CropLife International focused on ensuring the long term efficacy of insect, mite and tick control products through effective resistance management for sustainable agriculture and improved public health. A key function of IRAC is the continued development of the Mode of Action (MoA) classification scheme, which provides up-to-date information on the modes of action of new and established insecticides and acaricides and which serves as the basis for developing appropriate IRM strategies for crop protection and vector control. The IRAC MoA classification scheme covers more than 25 different modes of action and at least 55 different chemical classes. Diversity is the spice of resistance management by chemical means and thus it provides an approach to IRM providing a straightforward means to identify potential rotation/alternation options.